(untitled) (Coordinates of Public Administration, 2026)
The article, based on extensive factual material, examines the activities of the party and Soviet authorities of Soviet Ukraine regarding the training of personnel for collective farm construction during the 1930s. Certain changes in this period were observed in the technical equipment of agriculture. Improvements in technical provision made it possible to begin the mechanization of production processes in the second half of the 1930s. In most cases, machine operators were trained through short-term courses. By the end of the period under study, the agriculture of the Ukrainian SSR had not been sufficiently provided with personnel for collective farm construction, and these activities ultimately proved unsuccessful. The article investigates the operation of the courses, the composition of trainees, their social background, and the organizational system of training. The level of qualification of the teaching staff of the courses and their distribution across the territory of Soviet Ukraine are analyzed. These changes did not significantly improve the course-based training of managerial personnel, while the productivity of collectivized agriculture remained low. The consequences of the repressive policy of the Soviet authorities were tragic. кадрова policy did not produce substantial results. The tractorization of agriculture intensified, and the period of mass forced collectivization came to an end. Individual farms were completely eliminated. Collective farms became dominant in rural areas. During these years, the provision of agricultural machinery changed significantly, and almost all agricultural equipment was domestically produced. The main part of the machinery was concentrated in the hands of the state, which thereby tied weak collective farms to itself and extracted excessive profits from them through the use of machinery. The completion of collectivization did not mean the completion of the mechanization of agricultural production. By the end of the 1930s, the majority of agricultural work was still performed manually. The number of specialists involved in collective farm construction increased. They became the leading stratum of this system; however, they became detached from the land. They turned into state-employed workers cultivating the land without developing a sense of ownership or economic attachment to it.